Co-movement of output and price in Malaysia: Empirical evidence and macroeconomic policy implications - Abdul Manap, Turkhan Ali; Kassim, Salina (Universiti Teknologi MARA Terengganu, 2012)
This study conducts a comprehensive analysis on the output-price relationship in Malaysia with the objective of identifying the major source of macroeconomic fluctuations in Malaysia, thus drawing relevant policy recommendations for effective macroeconomic stabilization policy. We analyze the short- and long-run co-movements between real activity and prices using several tests in efforts to arrive at conclusive findings. Apart from the descriptive analysis, the study relies on the VAR forecast errors based on Den Haan and Sumner (2000). The study considers an extended data sample of monthly frequency covering the period from January 1971 to November 2009. The study aims to contribute towards enriching policy recommendations for effective macroeconomic stabilization policy in the country.